The recovering intoxication and its aftermath - Jamison, Leslie 1983- (Little, Brown and Company, 2018)
Presents an exploration of addiction that blends memoir, cultural history, literary criticism, and journalistic reportage to analyze the role of stories in conveying the addiction experience, sharing insights based on the lives of artists whose achievements were shaped by addiction.--
Keywords: Alkoholismus; Anonyme Alkoholiker; Jamison, Leslie / 1983- / Health; Addicts / Rehabilitation; Alcoholics / Rehabilitation; Substance abuse / Rehabilitation; Recovering addicts / Case studies; Recovering alcoholics / Case studies; BIOGRAPHY & AUTOBIOGRAPHY / Personal Memoirs; PSYCHOLOGY / Psychopathology / Addiction; BODY, MIND & SPIRIT / Healing / General; Health; Recovering addicts; Recovering alcoholics; Case studies; Autobiografie; Biografie